SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN BANK TERBAIK UNTUK PEMBUKAAN REKENING MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS (AHP): Metode Analytical Hierarchy Process - Supriatin, Atin; Yana, Adelia Alvi (Informatics and Computer Engineering Journal, 2022)
Banks are business entities that collect public funds as a place to carry out various financial-related transaction activities that people generally use to save money. There are many kinds of banks in Indonesia that offer all the advantages ranging from administration to the interest given to customers. It is very important in choosing a bank because the better the facilities and types of services provided by the bank, the greater satisfaction with the customer. The existence of a decision support system is a solution to provide public consideration in selecting the best bank for account opening. The method used in this research is the Analytical Hierarchy Process (AHP) method. Analytical Hierarchy Process (AHP) is a method of decision support system by using a hierarchy and making comparisons on each criterion and alternative that is considered in decision making. The final result of data management and testing of the AHP method was found that BCA had the most superior score of 35.80%, while BRI placed second with a value of 34.40%. Then the third position is Mandiri at 16.40% and the last is BNI at 13.40%.